Association Between p.R4810K Variant and Long-Term Clinical Outcome in Patients With Moyamoya Disease - Ge, Peicong; Ye, Xun; Liu, Xingju; Deng, Xiaofeng; Wang, Rong; Zhang, Yan; Zhang, Dong; Zhang, Qian; Zhao, Jizong (Frontiers in Neurology, 2019)
Objective: To estimate the association between p.R4810K variant and clinical outcomes of patients with moyamoya disease (MMD). Methods: The p.R4810K genetic variant was genotyped among 498 Chinese patients with MMD conducted from June 1, 2012, to June 31, 2017. Data was obtained by retrospective chart review, follow-up information and outcome were obtained through clinical visits and telephone. Results: Among 498 patients, 361 (72.5%) were wild-type patients (G/G), 133 (26.7%) heterozygous patients (G/A), and 4 (0.8%) homozygotes (A/A). Compared with GG group, the patients in the G/A+A/A group were younger at diagnosis and had more familial cases, more transient ischemic attack cases, more posterior cerebral artery involved hemispheres, less unilateral lesions. After the median 53 months follow-up, strokes occurred in 9 patients in the G/A+A/A group and in 52 in the G/G group. Multivariate Cox regression analysis showed that the history of hypertension (HR, 2.294; 95% CI, 1.251–4.206; p = 0.007), the presence of TIA (HR, 0.319; 95% CI, 0.120–0.846; p = 0.022), and the Suzuki stage (HR, 1.510; 95% CI, 1.129–2.018; p = 0.005) were associated with recurrent stroke. The p.R4810K (HR, 0.601; 95% CI, 0.292–1.239; p = 0.168) was not associated with recurrent stroke. Multivariate logistic regression analysis showed that recurrent stroke (OR, 5.997; 95% CI, 2.583 to 13.924; p = 0.000) was the only factor associated with unfavorable neurological status. And the p.R4810K (OR, 0.885; 95% CI, 0.482 to 1.627; p = 0.695) was not associated with neurological status. Conclusions: Compared to the patients in G/G group, patients in G/A+A/A group exhibited different clinical features, and had a lower rate of recurrent stroke and better clinical outcome after early medical and surgical interventions. Multivariate COX and logistic regression analysis showed that p.R4810Kvariant was not related to either recurrent stroke or neurological status. The p.R4810Kvariant may not be associated with long-term clinical outcome in Chinese patients with MMD.